Hubungan Olahraga dengan Kejadian Diabetes Melitus Tipe II di Wilayah Kerja Puskesmas Purwosari Surakarta - AROFAH, IKHTIYAROTUL, Bejo Raharjo, SKM, M.Kes, Farid Setyo Nugroho, SKM (2015)
ABSTRACT Diabetes Mellitus is a chronic disease that occurs when the body cannot produce enough insulin or cannot use insulin effectively, the disease is still a public health problem. The objectives of the research was to know the ratio between sports and the incidence of type II Diabetes Mellitus in Puskesmas Purwosari Surakarta area. The type of research was observational research with case control study design. Population of cases in this study were all patients with type II Diabetes Mellitus in March-May 2015, while population control is not the type II Diabetes Mellitus patients. Selection of the sample in the case group of 40 people and the control group as many as 40 people were done using simple random sampling technique while using a statistical test Chi Square test. Based on the findings in the case group obtained under five suffering from DM with sports for 27 people (67,5%) and in the control group who experienced sports for 14 (35%). Results of this study indicate that there is a relationship between sports and the incidence of type II Diabetes Mellitus in Puskesmas Purwosari Surakarta (p= 0.004; OR = 3.857; 95% CI = 1.526 to 9.750). Key Words: Sports and Diabetes Mellitus Type II